Effects of a tropical cyclone on salt marsh insect communities and post‐cyclone reassembly processes. Issue 6 (28th February 2020) - Chen, Xuan; Adams, Benjamin J.; Platt, William J.; Hooper‐Bùi, Linda M.
Abstract : Concepts regarding effects of recurrent natural disturbances and subsequent responses of communities are central to ecology and conservation biology. Tropical cyclones constitute major disturbances producing direct effects (damage, mortality) in many coastal communities worldwide. Subsequent reassembly involves changes in composition and abundance for which the underlying mechanisms (deterministic and stochastic processes) are still not clear, especially for mobile organisms. We examined tropical cyclone‐induced changes in composition and reassembly of entire insect communities in 16 Louisiana coastal salt marshes before and after Hurricane Isaac in 2012 and 2013. We used the Shannon index and multivariate permutational ANOVA to study insect resistance and resilience, β diversity partitioning to evaluate the importance of species replacement, and null models to disentangle the relative roles of different assembly processes over time after the tropical cyclone. The α diversity and species composition, overall and for different trophic levels, decreased immediately after the tropical cyclone; nonetheless, both then increased rapidly and returned to pre‐cyclone states within one year. Changes in species abundance, rather than species replacement, was the primary driver, accounting for most temporal dissimilarity among insect communities. Stochastic processes, which drove community composition immediately after the tropical cyclone, decreased in importance over time. Our study indicates that rapid reformation of insect communities involved sequential landscape‐level dynamics. Cyclone‐resistant life cycle stages apparently survived in some, perhaps random locations within the overall salt marsh landscape. Subsequently, stochastic patterns of immigration of mobile life cycle stages resulted in rapid reformation of local communities. Post‐cyclone direct regeneration of salt marsh insect communities resulted from low resistance, coupled with high landscape‐level resilience via re‐immigration. Our study suggests that the extent of direct regeneration of local salt marsh insect communities might change with the size of larger marsh landscapes within which they are imbedded.